Postural orthostatic tachycardia is not a useful diagnostic marker for chronic fatigue syndrome. (2nd October 2016) - Roerink, M. E.; Lenders, J. W. M.; Schmits, I. C.; Pistorius, A. M. A.; Smit, J. W.; Knoop, H.; van der Meer, J. W. M.
Abstract: Background: Postural orthostatic tachycardia syndrome (POTS) is considered a diagnostic marker for chronic fatigue syndrome (CFS). Objectives: The aims of this study were to (i) compare POTS prevalence in a CFS cohort with fatigued patients not meeting CFS criteria, and (ii) assess activity, impairment and response to cognitive behavioural therapy (CBT) in CFS patients with POTS (POTS‐CFS) and without POTS (non‐POTS‐CFS). Methods: Prospective cohort study at the Radboud University Medical Centre in the Netherlands. Between June 2013 and December 2014, 863 consecutive patients with persistent fatigue were screened. Patients underwent an active standing test, filled out questionnaires and wore an activity‐sensing device for a period of 12 days. Results: A total of 419 patients with CFS and 341 non‐CFS fatigued patients were included in the study. POTS prevalence in adult patients with CFS was 5.7% vs. 6.9% in non‐CFS adults ( P = 0.54). In adolescents, prevalence rates were 18.2% and 17.4%, respectively ( P = 0.93). Adult patients with POTS‐CFS were younger (30 ± 12 vs. 40 ± 13 years, P = 0.001) and had a higher supine heart rate (71 ± 11 vs. 65 ± 9 beats per min, P = 0.009) compared with non‐POTS‐CFS patients. Severity and activity patterns did not differ between groups. In patients with CFS, criteria for Systemic Exertion Intolerance Disease (SEID) were met in 76% of adults and 67% of adolescents. In these patients with CFS fulfilling the SEID criteria, the prevalence of POTS was not different from that in the overall CFS population. POTS‐CFS adolescents had less clinically significant improvement after CBT than non‐POTS‐CFS adolescents (58% vs. 88%, P = 0.017). Conclusion: In adults with CFS, the prevalence of POTS was low, was not different from the rate in non‐CFS fatigued patients and was not related to disease severity or treatment outcome. In POTS‐CFS adolescents, CBT was less successful than in non‐POTS‐CFS patients. The evaluation of POTS appears to be of limited value for the diagnosis of CFS.